Joint texture and depth map coding for error-resilient 3-D video transmission - Gao, Pan; Xiang, Wei; Rahaman, D. M. Motiur; Paul, Manoranjan (2017 IEEE International Conference on Image Processing (ICIP), 2017)
This paper addresses the problem of error-resilient source coding for 3-D video transmission over packet-loss networks. The proposed approach jointly optimizes the texture coding mode and the depth coding mode for each macroblock in the reference views. Firstly, a distortion model is developed to capture the effect of the texture distortion and depth distortion on the synthesized view. Then, joint optimization of texture and depth coding modes is derived based upon an operational rate-distortion framework using Lagrange multiplier method. In particular, a dual trellis-based algorithm is introduced in order to overcome the macroblock interdependencies of texture and depth map in the optimization procedure. Simulation results demonstrate that significant and consistent gains can be achieved over currently used techniques.